Outcomes of transcatheter aortic valve replacement in patients with cognitive dysfunction. Issue 5 (11th February 2021) - Jain, Vardhmaan; Kalra, Ankur; Panhwar, Muhammad Siyab; Bansal, Agam; Nowacki, Amy; Bhatia, Kirtipal; Gupta, Tanush; Ineman, Nichole L.; Khan, Safi U.; Krishnaswamy, Amar; Reed, Grant W.; Puri, Rishi; et al.
Abstract: Importance: The impact of pre‐existing cognitive dysfunction on outcomes after transcatheter aortic valve replacement (TAVR) remains unclear. Objective: To study the association between dementia and post‐TAVR outcomes. Design: Cohort study with propensity‐score matching was conducted using the Nationwide Inpatient Sample. Exposures: History of dementia at the time of undergoing TAVR. Main outcomes: All‐cause in‐hospital mortality, stroke, bleeding requiring transfusion, acute kidney injury, post‐procedural vascular complications, post‐procedural pacemaker implantation, length of stay, in‐hospital delirium, and discharge disposition in patients with and without dementia undergoing TAVR. Results: Of 57, 805 patients undergoing TAVR, 2910 (5.0%) had a diagnosis of dementia. Propensity‐score matching yielded 2895 matched pairs of patients. TAVR was associated with an increased risk of bleeding requiring transfusion (14.7% vs 8.6%, odd ratio (OR) 1.82 [95% confidence interval (CI) 1.26–2.63]; p < 0.01), discharge to a rehabilitation facility (45.8% vs 31.6%, OR 2.27 [95% CI 1.67–3.08]; p < 0.001), in‐hospital delirium (7.4% vs 3.6%, OR 2.13 [95% CI 1.26–3.61]; p < 0.01), increased length of stay (6.75 ± 0.07 days vs 6.11 ± 0.06 days, slope = 1.11 [95% CI 1.03–1.19]; p < 0.01), but comparable in‐hospital mortality (2.1% vs 2.6%, OR 1.26 [95% CI 0.57–2.79]; p = 0.57] in patients with dementia compared with patients without dementia. Conclusions and relevance: This study found that patients with dementia undergoing TAVR had a longer hospital stay as well as higher rates of discharge to a rehabilitation facility and in‐hospital delirium, which may indicate debility and functional decline during hospitalization; however, in‐hospital mortality and other outcomes were comparable between the two groups. TAVR candidates should be subjected to a comprehensive geriatric and cognitive assessment to help risk‐stratify them for potential post‐procedural functional decline. Prospective studies aimed at standardizing cognitive scoring and evaluating the post‐procedural quality of life are needed.